The nobility and ecclesiastical patronage in thirteenth-century England - Gemmill, Elizabeth (Boydell & Brewer, 2013)
"While there has been work on the nobility as patrons of monasteries, this is the first real study of them as patrons of parish churches, and is thus the first study to tackle the subject as a whole. Illustrated with a wealth of detail, it will become an indispensable work of reference for those interested in lay patronage and the Church more generally in the middle ages." Professor David Carpenter, Department of History, King's College London. This book provides the first full-length, integrated study of the ecclesiastical patronage rights of the nobility in medieval England. It examines the nature and extent of these rights, how they were used, why and for whom they were valuable, what challenges lay patrons faced, and how they looked to the future in making gifts to the Church. It takes as its focus the thirteenth century, a critical period for the survival and development of these rights, being a time of ambitious Church reform, of great change in patterns of land ownership in the ranks of the higher nobility, and of bold assertion by the English Crown of its claims to control Church property. The thirteenth century also saw a proliferation of record keeping on the part of kings, bishops and nobility, and the author uses new evidence from a range of documentary sources to explore the nature of the relationships between the English nobility, the Church and its clergy, a relationship in which patronage was the essential feature. Dr Elizabeth Gemmill is University Lecturer in Local History and Fellow of Kellogg College. University of Oxford.